Empathy in vaccination counselling: a survey on the impact of a three-day residential course - Massimo Maurici; Michele Arigliani; Valentina Dugo; Carlo Leo; Valentina Pettinicchio; Raffaele Arigliani; Elisabetta Franco (Taylor & Francis Group, 2019)
Background: In an era of hesitance to use vaccines, the importance of effective communication for increasing vaccine acceptance is well known. This study aimed to assess the impact of a three-day residential course concerning empathy and counselling abilities on patients' ratings of the level of empathy of physicians and nurses working in vaccination centers. Methods: The empathy of healthcare providers was evaluated using the Adapted Consultation and Relational Empathy (CARE) Measure. The survey involved 20 healthcare workers, doctors, and nurses in three immunization services of a Local Health Unit in South Italy. Before and after attending the course, all of them administered the questionnaire to 50 consecutive parents of vaccinated children. Statistical tests were used to assess the homogeneity of pre- and post -course samples, to measure the level of empathy perceived by parents in doctors and nurses in pre- and post-course evaluations, and to compare the average CARE Measure scores among groups. Results: Analysis of the questionnaires showed an increase of "excellent" scores and statistically significant differences between the pre- and post -course median values. Statistically significant differences between doctors and nurses were shown in almost all questions pre-course and in only four questions post-course. Conclusions: This study demonstrated that a residential course is effective at improving patient-rated empathy of doctors and nurses working in vaccination centers and could result in an increase of parents' adherence to vaccination programs.